Unwanted : a novel - Ohlsson, Kristina, 1979- (Emily Bestler Books/Atria, 2012)
Inspector Fredericka Bergman investigates the kidnapping and murder of a child who had been separated from her mother on a crowded train on a rainy Swedish summer day, a case that points to the work of a brilliant and ruthless killer.